FLASHCARD TO IMPROVE STUDENTS' VOCABULARY ABILITIES - Muhammad Rifai, Dian (Melekliterasi Press, 2024)
The aim of this research is to find out whether the use of flashcards can effectively improve students' mastery of English vocabulary in one of the elementary schools in Central Java by presenting interactive learning media using attractive visuals such as pictures that suit the character of early childhood children such as flashcard media. Researchers used a pre-experimental design with one pre-test post-test group to build quantitative research. Sugiyono (2016) defines pre-experimental design as a design that involves one group undergoing a pre-test and post-test. Because there are no control variables, in this study the researchers measured one group as subjects before and after being treated and included a pre-test and post-test. The researcher found that he use of flashcard really helps students improve their vocabulary mastery and makes it easier for students to remember vocabularies related to daily activities easily and quickly.